Analysis Financial Ratios to Stockprice Volatility Technology Sector Companies the Indonesian Stock Exchange (2022–2024) - Dewi Paramita; Retno Indah Hernawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the effect of financial ratios, namely Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA), on stock price volatility in technology companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. Using a quantitative approach and secondary data from annual financial reports on the website www.idx.co.id, this study purposively selected a sample of technology companies that met the data completeness criteria. This study found that a high DER increases stock price volatility due to financial risk, while a high CR and ROA reduce stock price volatility by indicating good liquidity and profitability. This study concludes that financial ratios play an important role in predicting and managing investment risk in the technology sector. Therefore, financial ratio analysis is an important tool in risk mitigation and making more prudent investment decisions in the technology sector for companies listed on the Indonesia Stock Exchange (IDX). Multiple linear regression analysis is the analysis technique used in this study, and the analysis tool used is IBM SPSS Statistics 25. The technology sector listed on the IDX for the 2022-2024 period is the population in this study, and the number of samples collected is 73 data obtained using purposive sampling.